RESPON PERTUMBUHAN DAN PRODUKSI KELAPA SAWIT PADA APLIKASI PUPUK PELEPAH - Yohana Theresia Maria Astuti; Tri Nugraha Budi Santosa; Dimas Deworo Puruhito; Latif Wrestiawan; Eddy Sugiharto; Y. Sugiyanto (AGROISTA : Jurnal Agroteknologi, 2018)
The study objective was to determine the response of growth and production of oil palm on frond fertilizer application. The duration experiment, from June 2017 to April 2018 at the Educational and Experimental Garden of the Stiper Agriculture Institute, Stiper Edu Agro Tourism (SEAT), Ungaran, Central Java, Indonesia. This study used an experimental method with a completely randomized factorial design. The first factor was the age of plants consisting of 2 levels for 6 years old plants and 12 years old plants. The second factor was the dose of frond fertilizer application with 3 levels of application. As control (5 kg/plant/year NPK fertilizer), 2 kg/plant/year frond fertilizer, 4 kg/plant/year frond fertilizer. The experiment using 7 replications for each combination treatment. The result on vegetative growth of oil palm showing the same effect on control and frond fertilizer applications. However, significant increase of production shown in the frond fertilizer application. The total weight of fresh bunches based on harvest observations in January, February, March and April 2018, the highest at the age of 6 years old oil palm which was given 2.0 kg/plant/year frond fertilizer (63.2 kg FFB/4 months). Oil palm productivity with an application of 2.0 kg/plant/year frond fertilizer showing result of 18.96 tons of FFB/ha/year. Compared this to the productivity of control with gain of 6 tons of FFB/ha/year. The highest average weight of fresh bunch in oil palm age 12 years in 4.0 kg frond fertilizer application, with average weight of fresh bunch was 14 kg. Keywords: oil palm, frond fertilizer, vegetative growth, productivity